PENURUNAN KECEMASAN REMAJA KORBAN BULLYING MELALUI TERAPI KOGNITIF - Betie Febriana (IJNP (Indonesian Journal of Nursing Practices), 2017)
Bullying causes many negative impacts to the victims, one of them is anxiety. Anxiety influence learning achievement for student. Therefore, it is important to take therapy to reduce anxiety. This study aims to determine the effectiveness of cognitive therapy in reducing anxiety in adolescents’ victims of bullying. Subjects in this study were SMA’S students who are victims of bullying. The research design used True Experimental Pre-Post Test With Control Group. Sample was 22 respondents with simple random sampling technique. Researchers used Olweus Bully / Victims Questionnaire to identify students who are victims of bullying and HARS (Hamilton anxietyrating scale) (rxx '= 0.617) to identify anxiety before and after therapy. The results of this study was cognitive therapy reduce anxiety level in adolescent’s victim of bullying (p-value= 0,002). Another finding in this study, there was a difference of quantitative meetings on respondents when getting therapy, it depends on the number of negative thoughts and the ability of respondents to control negative thoughts.